PREVALENCE OF UNCONTROLLED DIABETES AND ITS ASSOCIATION WITH LEFT VENTRICULAR DYSFUNCTION IN MYOCARDIAL INFARCTION (MI) PATIENTS (The Research of Medical Science Review, 2025)
OBJECTIVE: To evaluate the frequency of uncontrolled diabetes in individuals diagnosed with myocardial infarction (MI) at a tertiary healthcare center in Karachi, Pakistan, and to compare the incidence of left ventricular (LV) dysfunction between MI patients with uncontrolled and controlled diabetes.METHODOLOGY: A cross-sectional study was carried out at the Adult Cardiology Department of the National Institute of Cardiovascular Diseases (NICVD), Karachi. The study included 155 myocardial infarction patients, aged 18 to 65 years, of either gender. Blood samples were collected for HbA1c testing, and individuals with values greater than 7% were classified as having uncontrolled diabetes. Echocardiography was carried out to evaluate left ventricular performance, with an ejection fraction below 50% indicating dysfunction. The data were analyzed using SPSS version 26, and a 5% level of significance was applied.RESULTS: A cohort of 155 individuals diagnosed with myocardial infarction was analyzed (mean age 58.66 ± 9.45 years; 73.5% male). The prevalence of uncontrolled diabetes was noted in 76.8% of the cases examined. The average HbA1c level was markedly elevated within this cohort (9.35 ± 1.79% vs. 6.18 ± 0.52%, p < 0.001). No statistically significant variations were identified in LVEF (p = 0.418) or in the rates of LV dysfunction (p = 0.604) across the specified groups.CONCLUSION: This study found a high prevalence of poorly managed diabetes among the population experiencing myocardial infarction (MI). While LV dysfunction was noted more commonly in poorly-controlled diabetic patients, this association did not reach statistical significance. These findings reinforce the need for routine glycemic monitoring in individuals with MI, while also emphasizing the need for further study to evaluate the impact of poorly controlled glycemia on the heart.